Reaktualisasi Dakwah dalam Perspektif Al-Qur’an dan Sunnah di Era Digital: Pendekatan Etis, Komunikatif, dan Kontekstual - Ihsan Suri; Murodi; Rubiyanah; Muhtadi (STAI Bumi Silampari, 2026)
This study aims to analyze and reactualize the concept of Islamic preaching (da’wah) from the perspective of the Qur’an and Sunnah in the digital era through an ethical, communicative, and contextual approach. In Islam, da’wah is not merely a process of delivering religious messages but also a form of social communication grounded in Qur’anic moral and spiritual values. Using a qualitative library research method and hermeneutic analysis, this research examined more than thirty academic papers published between 2020 and 2025 that discuss Qur’anic da’wah and digital preaching practices. The findings reveal a paradigm shift in contemporary da’wah from monologic preaching toward dialogical, visual, and participatory forms through digital media such as YouTube, TikTok, and podcasts. Core Qur’anic values such as bil-hikmah (wisdom), mau’izhah hasanah (gentle advice), mujadalah billati hiya ahsan (constructive dialogue), and wasathiyah (moderation) remain the ethical foundation of digital da’wah communication. Moreover, digital da’wah plays a crucial role in strengthening religious moderation and enhancing Islamic literacy among younger generations, despite facing challenges such as misinformation and the commercialization of religion. This study proposes a conceptual model of Qur’anic da’wah in the digital era that integrates revelation, modern communication, and social responsibility.